Effect of high-dose intravenous vitamin C therapy on the prognosis in patients with moderately severe and severe acute pancreatitis: protocol of a prospective, randomized, double-blinded, placebo-controlled study - Sun, Wenwu; Zhao, Bing; Li, Jiaoyan; Wang, Yihui; Qi, Xing; Ning, Ning; Sun, Silei; Li, Mengjiao; Yao, Yi; Ni, Tongtian; Ma, Li; He, Juan; et al. (Frontiers in Medicine, 2023)
Intr oduction: Acute pancreatitis is a common gastrointestinal disease. The mortality of patients suffered with severe acute pancreatitis (SAP) remains high. It is unclear whether high dose intravenous vitamin C (HDIVC) therapy could improve the prognosis of these patients. The current prospective, randomized, double-blinded, placebo-controlled study will explore the effect of high This is a provisional file, not the final typeset article dose intravenous vitamin C therapy on the prognosis in patients with moderately severe and severe acute pancreatitis.Methods and design: 418 participants with moderately severe and severe acute pancreatitis that satisfy the eligible criteria will be randomized 1:1 to receive treatment with HDIVC (200mg/kg/24h) or placebo (saline) for 7 days. The primary outcome is 28 days mortality in these patients. The secondary outcomes include organ functions and interventions, laboratory test, healthcare and 90 days mortality.